EFEKTIFITAS PENGELOLAAN PERPUSTAKAAN SEBAGAI SUMBER BELAJAR BAGI WARGA BELAJAR DI PSBR RUMBAI - Rismaulina P Rismaulina P; Daeng Ayub Natuna; Widiastuti Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research start from some problem on the field, such as: 1)Low number of library visitor whether to read or borrow books 2)Low number of books series because there is no routine schedule to adding more books to support learning process 3)The service provided by the librarians are less attractive to make the library as a learning resource. This research uses descriptive research method with qualitative approach. The result showed that the procurement of library materials indicator in PSBR Rumbai is not effective yet, as seen from the failure of adding more books annually that have been planned since 2011 until now. Books regulating and maintaining indicator is not effective and efficient yet. Books in library have been classified but there still difficulity in finding books faced by visitors. Equipment of library room indicator is not adequate in terms of feasibility, facilities and infrastructure needs of the library. Reader service indicator by librarian is not effective yet in terms of time that giving by the librarian.Keyword: Effectiveness, Manajemen Library